Abnormal Head Position «Astrologer Posture» in Ophthalmology. Review - G. V. Gladysheva; N. V. Ananyeva; I. L. Plisov (Oftalʹmologiâ, 2024)
An abnormal or compensatory head posture occurs when the head deviates from its normal primary position. The cause can be ocular, orthopedic, and neurological. Since the etiology is not always obvious, such patients need to be carefully examined, and sometimes a multidisciplinary examination should be carried out. Compensatory head position in ophthalmology is usually an attempt to improve visual acuity or create binocularity. An abnormal head position can be manifested by a change in the position of the chin up, down, tilting the head to the right or left, turning the face to the right or left, or a combination of both. The purpose of our review is to provide literature data of the most common ophthalmic diseases in children, accompanied by a compensatory head position “astrologer posture”. Methods used to find, select and obtain information as well as to synthesize the data are information search on the Internet through Google Scholar, PubMed and eLibrary. Number of sources: 35 (from 1905 to 2022).